L'enquête sur la formation des restaurateurs dans l'Entre-Deux-Guerres: transformation d’un métier et reconnaissance d’une profession (1929-2011) - Pierre Leveau (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
This article explains how the inquiry on training for restorers commissioned by the International Museum Office (IMO) in 1932 finally led in 1981 the Committee for Conservation of the International Concil of Museums (ICOM-CC) to recognize the profession of conservator-restorer. It establishes that the regulation of the profession in Europe is the result of a process which started nearly a century ago. It thus fills a historiographical gap and reexamines the question of protecting the title of practitioners, still pending.